2011
DOI: 10.1164/rccm.201011-1802oc
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Cigarette Smoking and Acute Lung Injury after Severe Blunt Trauma

Abstract: Rationale: Cigarette smoking has been demonstrated in laboratory studies to have effects on lung epithelial and endothelial function similar to those observed in acute lung injury (ALI). However, the association between active and passive cigarette smoke exposure and susceptibility to ALI has not been prospectively studied. Objectives: We hypothesized that both active and passive cigarette smoke exposure would be associated with increased susceptibility to ALI after severe blunt trauma. Methods: We measured le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
126
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 40 publications
4
126
1
7
Order By: Relevance
“…The primary definition of grade 3 PGD at 48 or 72 hours after transplant was associated with a relative risk (RR) of 4.8 (95% CI, 3.3-7.0; P , 0.001) for death within 90 days of transplant compared with those without grade 3 PGD and an ARI of 18% (95% CI, 12-24). Grade 3 PGD was associated with a significantly increased 1-year mortality (RR, 3.0; 95% CI, 2.3-3.9; P , 0.001) compared with those without grade 3 PGD, and an ARI of 23% (95% CI, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Although the magnitude of the association between grade 3 PGD and mortality was attenuated when the alternate definition of any grade 3 PGD within 72 hours was used in the sensitivity analyses, the association remained significant at 90 days (RR, 3.5; 95% CI, 2.3-5.1; P , 0.001) and 1 year (RR, 2.5; 95% CI, 1.9-3.3; P , 0.001) (see Table E6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary definition of grade 3 PGD at 48 or 72 hours after transplant was associated with a relative risk (RR) of 4.8 (95% CI, 3.3-7.0; P , 0.001) for death within 90 days of transplant compared with those without grade 3 PGD and an ARI of 18% (95% CI, 12-24). Grade 3 PGD was associated with a significantly increased 1-year mortality (RR, 3.0; 95% CI, 2.3-3.9; P , 0.001) compared with those without grade 3 PGD, and an ARI of 23% (95% CI, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Although the magnitude of the association between grade 3 PGD and mortality was attenuated when the alternate definition of any grade 3 PGD within 72 hours was used in the sensitivity analyses, the association remained significant at 90 days (RR, 3.5; 95% CI, 2.3-5.1; P , 0.001) and 1 year (RR, 2.5; 95% CI, 1.9-3.3; P , 0.001) (see Table E6).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of this association are unclear, but cigarette exposure may result in increased oxidative injury and nicotine exacerbates reperfusion injury in experimental models (23). Because smoking status has recently been shown to increase the risk of ALI in trauma patients, it is plausible that tobacco smoke exposure in the donor lung might exacerbate lung injury that occurs at the time of allograft reperfusion (24). However, given the limited pool of available lung donors, it is not currently feasible to exclude patients who were previous smokers as potential lung donors.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers are more likely to be classified as non-smokers than the other way around. [11] Calfee et al, found 41% of patients demonstrated to be active smokers based on cotinine levels were not documented as such in the chart.…”
mentioning
confidence: 99%
“…To the best of our knowledge, only two other studies have looked specifically at the trauma population when assessing the risks of smoking. Calfee et al [11] followed severe blunt trauma patients for the development of acute lung injury (ALI). To accurately identify, the smoking cohort, plasma cotinine levels were measured upon patient's arrival to the emergency department.…”
mentioning
confidence: 99%
“…The interaction between cigarette smoke exposure and ozone is also interesting. Cigarette smoke has recently been identified as an independent risk factor for ARDS in several at-risk populations (11)(12)(13), and is believed to have many of the same pathophysiologic effects on the lung as air pollution. It is possible that cigarette smoke and ozone have synergistic effects on the lung.…”
Section: It's In the Air We Breathementioning
confidence: 99%